2016
DOI: 10.1002/ejlt.201600072
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of water and acetone extracts of Fucus vesiculosus on oxidative stability of skin care emulsions

Abstract: A water and an acetone extract of the Icelandic brown algae Fucus vesiculosus were evaluated as potential natural sources of antioxidant compounds in skin care emulsions. To assess their efficacy in inhibiting lipid oxidation caused by photo-or thermoxidation, they were stored in darkness and room temperature as control conditions, and compared to samples stored under accelerated conditions (light and room temperature, or darkness and 40°C). The presence of extracts in the skin care emulsions induced remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…It was not surprising that exposure to light increased PV significantly to 20 meq kg −1 after 2 months of storage. This pattern was observed in other studies (Poyato et al, 2017;Thomsen, Horn, et al, 2017;. GC-MS analysis of the volatile compounds confirmed that lipid oxidation occurred only to a limited extent.…”
Section: Lipid Oxidation In Productssupporting
confidence: 87%
See 1 more Smart Citation
“…It was not surprising that exposure to light increased PV significantly to 20 meq kg −1 after 2 months of storage. This pattern was observed in other studies (Poyato et al, 2017;Thomsen, Horn, et al, 2017;. GC-MS analysis of the volatile compounds confirmed that lipid oxidation occurred only to a limited extent.…”
Section: Lipid Oxidation In Productssupporting
confidence: 87%
“…In earlier studies, it was clearly demonstrated that lipid oxidation can occur in topical skin formulations with either high or low lipid content and that their sensory quality can be affected by lipid oxidation as changes in both odor and color were observed (Malinowska, Gliszczynska‐Swiglo, & Szymusiak, ; Poyato et al, ; Thanonkaew, Wongyai, Decker, & McClements, ; Thomsen, Horn, et al, ; Thomsen, Hyldig, Taylor, Blenkiron, & Jacobsen, ; Thomsen, Taylor, et al, ). It is tempting to assume that the extent of lipid oxidation will decrease with decreasing lipid content.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of Poyato et al () a similar experiment was carried out for F. vesiculosus extracts (acetone and water) added to facial cream in concentrations of 1 and 2 g kg −1 cream (0.1% and 0.2%). In the present study, we wanted to evaluate lower concentrations of WE and also include an EE because previous studies have shown very similar antioxidant activity, both in vitro and in food systems, and chemical composition of ethanol and acetone extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, both water and ethanolic extracts (WE and EE) from Icelandic F. vesiculosus were able to prevent lipid oxidation in different food systems and cosmetic emulsions due to a high content of phlorotannins found in the seaweed species (Hermund et al, ; Honold et al, ; Karadag et al, ; Poyato et al, ). In those studies, it was concluded that the antioxidant efficacy of the F. vesiculosus extract is highly dependent on its in vitro antioxidant properties, because different antioxidant properties are required to protect complex food systems or cosmetic emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Plant seed oils are a combination of triglycerides of higher saturated and unsaturated fatty acids . The antioxidant properties that present naturally in plant seed oils can provide skin protection against reactive oxygen species (ROS), synergistically improving the photoprotective properties of the formulation . Thus, it shows great potential in developing a new photoprotective product taking into account the safe use of UV filters by incorporating bio‐oil from plant seed.…”
Section: Introductionmentioning
confidence: 99%